Mapping Land Potential and Carrying Capacity for Cattle Breeding Area Development - Arini, Audi Cindra; Safitri, Isti Farin Oktafia; Aini, Maulidya Nur (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Resources have a crucial role in maintaining the sustainability of human life and the surrounding ecosystem Malang Regency one of the regions with the largest number of beef cattle in Indonesia has great potential to support the growth of the livestock sector with 234 481 beef cattle and is ranked fifth nationally Optimal support especially land carrying capacity is the key to maximizing the potential of the livestock sector The establishment of a livestock area in Tumpang District is a strategic step to increase production capacity and availability of animal feed This research uses a Mixed Methods method with a spatial approach involving data analysis such as unsupervised classification evaluation of natural forage potential and calculation of the Forage Carrying Capacity Index IDD The findings show that all villages in Tumpang District have an IDD above 2 so they are categorized as safe With several potential villages such as Pulungdowo Duwet Krajan and Bejor With these findings strategic steps can be taken to utilize this potential sustainably to increase the contribution of the livestock sector in Malang Regency < em>< p>